Cross?cultural debugging and reliability and validity evaluation of The ConCom Safety Management Scale. - Yang Shuxian; Yang Hui (Chinese Nursing Research, 2020)
Objective: Cross-cultural adjustment and reliability and validity tests on the ConCom Safety Management Scale(CCSM) were carried out to provide measurement tools for evaluating head nurses' safety management level and practice in China. Methods: Following the principle of cross-cultural adjustment of the scale, the English CCSM scale was translated, back-translated and cross-culturally debugged. The Chinese version of CCSM was used to test 384 nurses to verify its reliability and validity. Results: The Chinese version of the CCSM scale consisted of 31 entries in 5 dimensions. The internal consistency Cronbach's α coefficient value was 0. 976, and the test-retest reliability was 0. 963. The content validity(S-CVI) was 0. 851; the exploratory factor analysis extracted 5 common factors, and the cumulative variance contribution rate was 73. 752%. The results of confirmatory factor analysis showed the fitness of the model for nurse managers were good. Conclusion: The Chinese version of CCSM scale has good reliability and validity and can be used for the evaluation of the safety management level and practice of head nurses in China.